Strategi Dinas Perhubungan dalam Mengatasi Kemacetan Lalu Lintas di Kota Bekasi - Khoirunissa, Okta; Purnamasari, Hanny (Universitas Terbuka, 2024)
One of the most populous places, Bekasi City, yet struggles with traffic. In urban centers, congestion often occurs at regular times, especially during commuting times, weekends, and holidays. Congestion has many negative effects.The present study employs a descriptive qualitative methodology to investigate the contextual factors of the issue and evaluate the Transportation Agency's approaches to mitigating traffic congestion in Bekasi City.Interview, observation, and documentation are the three main components of the information collection method. The study shows that the strategy of the Transportation Agency to address traffic congestion in Bekasi City has not been successful. This is shown by the Transportation Agency's Organizational Strategy which aims to encourage Dishub field officers to crack down or punish traffic violators, but it does not happen. Programs such as the Road Equipment Program, Traffic Management and Engineering Program, and Parking Facility Control Program are considered successful based on the approach applied by the government. However, these strategies faced several problems. One of them is the disproportionate growth of vehicles compared to the construction of new roads, which still causes congestion. According to the supporting strategies, the work quality of field officers should be improved as there is still a shortage of officers in some locations. Keywords: policy, strategy, traffic jams